RURAL RADIO RULES THE AIRWAVES - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Ahmadou Batoure, Deputy Director of Radio Rurale de Tchad, N'Djamena, Chad: 'Allow me to present my compliments tothe managers of CTA for the warm welcome they gave to the delegation of African journalists during their visit to CTA,organized by...